Hubungan Suhu dan Kelembaban Udara dan Intensitas Pencahayaan Dengan Sick Building Syndrome di SMA Negeri 3 Surakarta - Izharulhaq, Rifat Abhinaya; Fauzi, Rachmawati Prihantina; Mulyani, Sri (Journal of Applied Agriculture, Health, and Technology, 2024)
Sick Building Syndrome is a health symptom that is related to how long room occupants spent their time doing activities in a room. Several sick building syndrome symptoms were found among students of State Senior High School 3 of Surakarta like headache and sleepiness. The aim of this study was to analyze the relationship between the temperature, air humidity and light intensity of the classrooms with sick building syndrome symptoms on the students. The population were the students of grade XI and XII with the total of 840 students and the sample of 90 students taken using the random cluster sampling method. The measuring devices used were room thermometer, hygrometer, lux meter and SBS questionnaire. Termometer to measure temperature, a hygrometer to detect humidity, a luxmeter to measure illumination, and an SBS questionnaire to assess SBS symptoms. Rank Spearman correlation test was used to measure the correlation between room temperature, air humidity and light intensity with sick building syndrome symptoms found on students. The result of correlation test between room temperature with sick building syndrome showed a significant correlation with p value = 0,004 and r value = 0,402. The result of correlation test between air humidity with sick building syndrome showed a significant correlation with p value = 0,003 and r value = 0,440. The result of correlation test between light intensity with sick building syndrome showed a significant correlation with p value = 0,001 and r value = -0,683. This study concluded that there was a significant correlation between room temperature, air humidity, and light intensity with with sick building syndrome symptoms on the students of Senior High School State of 3 Surakarta.